2013
DOI: 10.1111/jpi.12087
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates secondary brain damage and neurobehavioral dysfunction after experimental subarachnoid hemorrhage: possible involvement of TLR4‐mediated inflammatory pathway

Abstract: Previous studies proved that melatonin protected against secondary brain damage by modulating oxidative stress after experimental subarachnoid hemorrhage (SAH), but it has not been evaluated yet about its effects on inflammatory pathway and secondary cognitive dysfunction in SAH model. This study was undertaken to evaluate the influence of melatonin on toll-like receptor 4 (TLR4) signaling pathway and neurobehavioral tests after SAH. Adult SD rats were divided into four groups: control group (n = 20), SAH grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 26 publications
3
69
0
1
Order By: Relevance
“…Therefore, terminating the translocation process of the activated NF-κB can intervene numerous genes transcription related to inflammation and, finally, mitigate SAH-related EBI. Previous studies have reported that some antioxidant agents or interval aimed at scavenging ROS exert positive results in experimental SAH, which is associated with inactivation of NF-κB [74,75,70,76]. Consistent with previous results, our findings showed that HS inhibited the nuclear translocation of p65 from cytoplasm; in addition, the gene expression of pro-inflammatory factors IL-1β, IL-6, and TNF-α elevated after SAH onset and suppressed by HS treatment, suggesting an inhibitory effect of HS on NF-κB activity and subsequent inflammatory response post-SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, terminating the translocation process of the activated NF-κB can intervene numerous genes transcription related to inflammation and, finally, mitigate SAH-related EBI. Previous studies have reported that some antioxidant agents or interval aimed at scavenging ROS exert positive results in experimental SAH, which is associated with inactivation of NF-κB [74,75,70,76]. Consistent with previous results, our findings showed that HS inhibited the nuclear translocation of p65 from cytoplasm; in addition, the gene expression of pro-inflammatory factors IL-1β, IL-6, and TNF-α elevated after SAH onset and suppressed by HS treatment, suggesting an inhibitory effect of HS on NF-κB activity and subsequent inflammatory response post-SAH.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in proinflammatory cytokines, including TNF-nflammatory cy-1β (IL-1β) and IL-6, is observed acutely after SAH [6]. The potential mechanisms underlying the upregulation of proinflammatory cytokines involve the activation of nuclear factor-κB (NF-κB) and the activation of the mitogenactivated protein kinase pathway and toll-like receptor 4 (TLR4) signaling pathway [6][7][8]. Recently, a study focused on the inflammasome axis, which controls the maturation and release of pro-inflammatory cytokines, demonstrated neuroprotective effects in early brain injury after SAH [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent progress in microsurgical and endovascular surgical techniques, the outcome of patients who suffer a SAH remains unsatisfactory [2]. SAH is a complex clinical disease that early brain injury (EBI) is the main aspect which affect patients' outcome [3].…”
Section: Introductionmentioning
confidence: 99%